2016
DOI: 10.14569/ijacsa.2016.070765
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Multi-criteria Decision Making in Software Engineering

Abstract: Abstract-Every complex problem now days require multicriteria decision making to get to the desired solution. Numerous Multi-criteria decision making (MCDM) approaches have evolved over recent time to accommodate various application areas and have been recently explored as alternative to solve complex software engineering problems. Most widely used approach is Analytic Hierarchy Process that combines mathematics and expert judgment. Analytic Hierarchy Process suffers from the problem of imprecision and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Faundes et al [23] suggested a fuzzy decision-making system-based approach for selecting components that evaluate and compare commercial off-the-shelf (COTS) and their impact on IT organizations. Kaur and Singh [24] introduced PROMETHE, a method for evaluating and selecting components that consider various quality attributes important for selecting COTS components, including reliability, integrability, performance, cost, and maintainability. Nazir et al [25] suggested using the analytic network process (ANP) to select components, considering criteria such as effectiveness, efficiency, satisfaction, safety, and usability.…”
Section: Selection Methods/approaches and Mcdm Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Faundes et al [23] suggested a fuzzy decision-making system-based approach for selecting components that evaluate and compare commercial off-the-shelf (COTS) and their impact on IT organizations. Kaur and Singh [24] introduced PROMETHE, a method for evaluating and selecting components that consider various quality attributes important for selecting COTS components, including reliability, integrability, performance, cost, and maintainability. Nazir et al [25] suggested using the analytic network process (ANP) to select components, considering criteria such as effectiveness, efficiency, satisfaction, safety, and usability.…”
Section: Selection Methods/approaches and Mcdm Techniquesmentioning
confidence: 99%
“…Thus, three papers were found to be completely irrelevant for software component selection. Airline reservation system UNHOS Yes Yes Gupta et al [41] System prototype FMP Yes Yes Nazir et al [42] Hypothetical case study OTSO and fuzzy logic Yes Yes Zhiqiao et al [43] Mail server system Lagrange relaxation decomposition with heuristic Yes Yes Khan and Mahmood [44] Meeting scheduling system Cluster-based component selection Yes Yes Gupta et al [45] ERP software FMOP Yes Yes Becker et al [46] Different real-world case Methodical analysis approach Yes Yes Kuar and Singh [24] General software systems PROMETHEE Yes Yes Nazir et al [25] Different ERP software ANP Yes Yes Kuar and Tomar [19] .Net software Pre-emptive goal programming Yes Yes Vescan [47] Reservation system Evolutionary-based algorithm Yes Yes Kaur and Tomar [48] Set of sorting and searching components Four-tier architecture technique Yes Yes Kaur and Tomar [27] Document manager Fuzzy clustering Yes Yes Vescan and S ¸erban [49] Reservation system Multi-objective optimization approach Yes Yes Verma and Mehlawat [50] Numerical illustration of software application Combined MCDM-AHP model Yes Yes Khan et al [51] Bounty rescue step game Multi-agent approach Yes Yes Sekar et al [52] Technology gallery K-means clustering, rank order clustering and similarity-based coefficients Yes Yes Chatzipetrou et al [53] Different types of components CoDA Yes Yes Roopa and Reddy [54] SMEs software system Computational algorithm Yes Yes Mehlawat et al [13] E-commerce software TOPSIS Yes Yes Gusev et al [55] Digital psychological tools Mathematical model Yes Yes Garg [56] E-payment system FMDBA Yes Yes Table 2 provides a summary for various software components, their associated methods/approaches, evaluation criteria, and the MCDM techniques employed for analysis. Each column in the table represents specific information to the body of knowledge.…”
Section: Data Extractionmentioning
confidence: 99%
“…They have attempted to quantify the performance of the various software quality models such as McCall (McCall et.al, 1977), ISO-9126 (Behkamal et.al, 2009), FURPS (Al-Qutaish, 2010), Boehm (Boehm et.al, 1978), and Dromey (Dromey, 1995) based on several factors such as reliability, efficiency, integrity etc. In (Sehra, 2016), the authors have presented various fields of application of MCDM algorithms in the domain of software engineering. Apart from this, they have also compared the performance of AHP and fuzzy AHP to choose the software quality model based on only three criteria reliability, efficiency and maintainability.…”
Section: Related Workmentioning
confidence: 99%
“…AHP can be used for various applications such as Strategic Planning, Resource allocation, and Resource selection [10]. The application has predominantly been observed in the realms of engineering, as well as personal and social categories, in terms of its wide-ranging applicability [11]. This observation can prove valuable to evaluate the suitability of employing AHP in specific areas of interest.…”
Section: Introductionmentioning
confidence: 99%